Figure 1 from VCAM-1–targeted MRI Improves Detection of the Tumor-brain Interface - Vinton W.T. Cheng (15020397) (2025)
Microvascular and tumor cell biology at the tumor rim in MDA231Br-GFP brain metastases. Representative histologic sections of rat brains, intrastriatally injected with MDA231Br-GFP tumor cells, from the tumor core, tumor rim, and the contralateral striatum, with corresponding box and whisker plots of marker expression in each region. Data shown as median ± interquartile range. Sections were immunohistochemically stained (brown) for tumor cell marker vimentin (A), endothelial marker CD31 (B), cell adhesion molecule VCAM-1 (C), cell proliferation marker Ki67 (D), and two stemness markers: SOX2 (E) and nestin (F). Scale bar = 100 μm. *, P < 0.05; ***, P < 0.001; n = 8; post hoc Bonferroni multiple comparison test for tumor cell density and microvessel density, and post hoc Dunn test for VCAM-1 expression. Tumor core was delineated from the infiltrative border as indicated by the blue and red lines, respectively. Expression of Ki67, nestin and SOX2 has been normalized to tumor area. *, P < 0.05; ***, P < 0.001; matched Wilcoxon test.